Status Epilepticus Australasian Registry for Children: A pilot prospective, observational, cohort study of paediatric status epilepticus. (25th April 2022) - Furyk, Jeremy S; George, Shane; Phillips, Natalie; Emeto, Theophilus I; Watt, Kerrianne; O'Brien, Sharon; Riney, Kate; Wilson, Catherine; Hearps, Stephen JC; Borland, Meredith L; Dalziel, Stuart R; Babl, Franz E; et al.
Abstract: Objective: Paediatric status epilepticus (SE) has potential for long‐term sequelae. Existing data demonstrate delays to aspects of care. The objective of the present study was to examine the feasibility of collecting data on children with paediatric SE and describe current management strategies in pre‐hospital and in‐hospital settings. Methods: A pilot, prospective, observational cohort study of children 4 weeks to 16 years of age with SE, in four EDs in Australia. Clinical details including medications administered, duration of seizure and short‐term outcomes were collected. Follow up occurred by telephone at 1 month. Results: We enrolled 167 children with SE. Mean age was 5.4 years (standard deviation [SD] 4.1), and 81 (49%) male. Median seizure duration was 10 min (interquartile range 7–30). Midazolam was the first medication administered in 87/100 (87%) instances, mean dose of 0.21 mg/kg (SD 0.13). The dose of midazolam was adequate in 30 (35%), high (>0.2 mg/kg) in 44 (51%) and low (<0.1 mg/kg) in 13 (15%). For second‐line agents, levetiracetam was administered on 33/55 (60%) occasions, whereas phenytoin and phenobarbitone were administered on 11/55 (20%) occasions each. Mean dose of levetiracetam was 26.4 mg/kg (SD 13.5). One hundred and four (62%) patients were admitted to hospital, with 13 (8%) admitted to ICU and seven (4%) intubated. Conclusion: In children presenting with SE in Australia medical management differed from previous reports, with midazolam as the preferred benzodiazepine, and levetiracetam replacing phenytoin as the preferred second‐line agent. This pilot study indicates the feasibility of a paediatric SE registry and its utility to understand and optimise practice. Abstract : Existing data on paediatric status epilepticus (SE) are limited. This pilot, prospective observational study of children in 4 EDs in Australia contributes valuable data on 167 children with SE. Our data suggest practice change in Australia with midazolam and levetiracetam increasingly used in Australian EDs.